Inter-correlation between Human Rights and Environmental Justice: A Discourse of Right to a Good and Healthy Environment in Indonesia - Yuliyanto, Eko; Alatiqoh, Maftukhatul Muna; Alfaruq, Ahmad Husain (Faculty of Law, Universitas Negeri Semarang, 2022)
The right to a good and healthy environment is part of human rights. Where the right to the environment as a human right to live in an environment with a minimum quality that allows the realization of a dignified and prosperous life. As part of human rights, the state must respect, fulfill, and protect the right to a good and healthy environment. To fulfill the right to a good and healthy environment, everyone is given the right to obtain environmental education, access to information, access to participation, and access to justice. In other words, without access to information, participation, and justice, the right to a good and healthy environment will be difficult to fulfill. The government needs a mechanism or instrument for these three accesses to fulfill the right to a good and proper environment for its citizens. In the next section, we will review mechanisms or instruments for access to information, as an effort to fulfill the right to a good and healthy environment, especially in the context of controlling air pollution, as well as the shortcomings and alternatives of these mechanisms or instruments. This study aims to analyze the discourse on the right to a good and healthy environment in Indonesia in the study of human rights and environmental law in Indonesia.